THE PHARMACOECONOMIC IMPACT OF GASTRO-PROTECTIVE AGENTS AT A TERTIARY CARE HOSPITAL - KULKARNI, NIRUPAMA; RASI, MOPIDEVI; NIZAR, NAZARIYA; DAVID, NISHOJA; N BALI, PRASAD; I DALAL, VARSHA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The study aimed to evaluate the pharmacoeconomic impact of gastro-protective agents (GPA) by carrying out cost-benefit analysis (CBA) and cost-effective analysis (CEA). Methods: This prospective observational study was carried out by simple randomization technique at Karnataka Institute of Medical Science, Hubballi. Data used were socio-economic details based on modified B. G Prasad scale. Current Index of Medical Specialists updated version March 2021 was used for CBA and CEA. Regression analysis was the statistical tool used in the study. Results: A total of 120 participants were included in the study. 57.5% were male and 42.5% were female. 3.33% were pediatrics, 32.5% were young adults, 37.5% were elder adults and 26.67% were geriatrics. Out of 120 samples, 94 participants were prescribed with pantoprazole, other drugs prescribed include domperidone and pantoprazole, rabeprazole, and ranitidine. The CBA revealed ratio of benefits over costs for pantoprazole was 3.86, ranitidine was 9.31, pantoprazole and domperidone was 0.84 and rabeprazole was 0.84. Additional cost of 138.30 Indian Rupee must be spent on pantoprazole over ranitidine to get cost-effective treatment without disease for one whole year. Conclusion: The CBA revealed that maximum patients received benefits for pantoprazole. CEA gives an idea on best effective treatment over two drugs of different class. Our study concludes that pantoprazole is deemed to be superior over other drugs of GPA prescribed among study participants.